Pengembangan Media Pembelajaran Tematik Menggunakan Aplikasi Macromedia Flash untuk Menanamkan Karakter Positif - Azrianti, Vivi Putri; Sukma, Elfia (Universitas Negeri Padang, 2021)
This research aims to develop thematic learning media using theapplication Macromedia Flash.Learning media that is more varied and interesting by combining folklore with positive moral values and developed through applications that are easy to use with the help of the latest technology according to the times. This research was conducted on students in grade IV SDN 48 Ganting, using the development method of the 4D model ( define , design, development and dessiminate).Based on the results of research that has been done, it is stated that the media are considered valid by the material experts and media experts. The results of the assessment questionnaire by the two experts showed a very valid media category with a total score of both (92.72%). After the assessment by the two media experts was judged to be very practical based on the results of the student response questionnaire, learning was considered very interesting when using media. The results of student responses obtained data of 19 students with a total value of 96%. In addition to student responses stating that this media is very practical, from the teacher's response to the number of school grades 95%. After distributing the questionnaire to the first school, the distribution of media was carried out at the next school, so it was also stated that learning media using macromedia flash was very practical with an acquisition of 89%. Based on the assessment of the questionnaires distributed states that the media is very practical and valid for instilling positive character in students.